2017
DOI: 10.3389/fpsyg.2016.02005
|View full text |Cite
|
Sign up to set email alerts
|

Structural Principles or Frequency of Use? An ERP Experiment on the Learnability of Consonant Clusters

Abstract: Phonological knowledge of a language involves knowledge about which segments can be combined under what conditions. Languages vary in the quantity and quality of licensed combinations, in particular sequences of consonants, with Polish being a language with a large inventory of such combinations. The present paper reports on a two-session experiment in which Polish-speaking adult participants learned nonce words with final consonant clusters. The aim was to study the role of two factors which potentially play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The N400 shows increased amplitude when the integration of word meaning in a given context is more problematic, such as when a semantically incongruent word is placed within a sentence (e.g., “The pizza was too hot to cry ” vs. “The pizza was too hot to eat ”). The N400 for words may be experimentally elicited in sentence context, as in the previous example (e.g., Van den Brink and Hagoort, 2004; Laszlo and Federmeier, 2009; Brunellière and Soto-Faraco, 2015; Payne et al, 2015), or by priming techniques (e.g., Holcomb and Neville, 1990; Desroches et al, 2009; Robson et al, 2017; Wiese et al, 2017; Haebig et al, 2018). These techniques use a prime word or a prime picture followed by the target word, with prime-target pairs being either semantically congruent or incongruent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N400 shows increased amplitude when the integration of word meaning in a given context is more problematic, such as when a semantically incongruent word is placed within a sentence (e.g., “The pizza was too hot to cry ” vs. “The pizza was too hot to eat ”). The N400 for words may be experimentally elicited in sentence context, as in the previous example (e.g., Van den Brink and Hagoort, 2004; Laszlo and Federmeier, 2009; Brunellière and Soto-Faraco, 2015; Payne et al, 2015), or by priming techniques (e.g., Holcomb and Neville, 1990; Desroches et al, 2009; Robson et al, 2017; Wiese et al, 2017; Haebig et al, 2018). These techniques use a prime word or a prime picture followed by the target word, with prime-target pairs being either semantically congruent or incongruent.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have addressed both phonological grammaticality and lexicality by combining illegal sequences, pseudowords and words – the latter congruent and incongruent with the semantic context (Friedrich and Friederici, 2005; Becker et al, 2014; Gansonre et al, 2018), but phonotactic frequency has been left out from the comparison. Studies focusing on phonotactic frequency, on the other hand, have shown that it impacts learning (Gonzalez-Gomez et al, 2013), word likeness judgments (Bailey and Hahn, 2001), pseudoword repetition (Vitevitch and Luce, 1998, 1999, 2005), ERPs (Bonte et al, 2005, 2007; Hunter, 2013; Wiese et al, 2017), and the dynamics of brain connectivity (Gow and Olson, 2015). Moreover, several studies have focused on the processing of real words only (e.g., Payne et al, 2015), or on legal versus illegal sound combinations (e.g., Domahs et al, 2009; Rossi et al, 2011), and a detailed account of the interplay of phonological grammaticality, lexicality and phonotactic frequency during the time course of word processing has not yet been provided.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also investigated the interaction between well-formedness and the frequency of clusters in the lexicon using attested and unattested clusters. The results showed distinct but interacting responses to well-formedness and attestedness (see also Wiese, Orzechowska, Alday, & Ulbrich (2017) for a study of Polish). In a passive-listening EEG study in English, White and Chiu (2017) also observed distinct responses to the attestedness of CC onsets and their well-formedness.…”
Section: Discussionmentioning
confidence: 90%
“…The role of sonority was also studied in ERP experiments. Electrophysiological responses to well-and ill-formed final clusters in Polish [27] and German [24] demonstrated the main effect of sonority in German speakers, and lowered sensitivity to sonority violations in Polish speakers. That is, the learning process at the neuro-physiological level is strongly affected by sonority in a phonotactically simpler language.…”
Section: Phonotactics: State Of the Artmentioning
confidence: 89%